A novel design methodology for osseointegrated implants and the effects of heat-treatment on shape setting nitinol foil - Morrone, Adam, author; Simske, Steven, advisor; Popat, Ketul, committee member; Kawcak, Christopher, committee member (Colorado State University. Libraries, 2020)
Nitinol, approximately equiatomic nickel and titanium and a popular shape memory alloy, has been used extensively in modern, implantable medical devices due to its natural biocompatibility, remarkable shape memory properties, and superelasticity. Much of the current literature on processing and handling this material focuses on thin wires, as this is what has historically been of most interest (e.g. for orthopedics, orthodontia, and orthognathics); however, as this technology advances, there are emerging applications of nitinol that require other form factors such as films and foils. In addition, although many manufacturers can produce three-dimensional nitinol structures, much of the information on shaping techniques is still proprietary. In an effort to fill these gaps in the literature and add to the knowledge of nitinol shaping techniques, this study compares the effects of various heat-treatments on the shape-setting of nitinol foil. Foils of two different NiTi compositions (50.2 and 50.8 percent Ni by atomic mole fraction) were rigidly fixed into a cylindrical shape and heat-treated at five different temperatures (400, 450, 500, 550, and 600 degrees C) and for five different durations (5, 10, 15, 20, and 25 minutes). The morphological rebound of these samples was evaluated, and a model was developed to described this shape setting behavior. In addition, the Austenite finishing temperature (Aƒ), and fatigue effects of all samples were evaluated to further quantify the effects of heat-treatment. The results from this materials study were then used in part to develop a novel design methodology for osseointegrated implants. Devices using this methodology have anchors that deploy from the main body to lock the implant in place. The contact points act as "active sacrificial zones" which can experience bone resorption without losing rigidity, while the remainder of the implant body undergoes normal loading conditions. This methodology aims to improve the quality and speed of bone ingrowth.
Keywords: heat-treatment; nitinol; osseointegration; NiTi; bone implants; OIP